IDENTIFICATIONOF ISOLATED FUNGI FROM SKIPJACK (Katsuwonus pelamis) KATSUOBUSHI DURING FERMENTATION - Gultom, Debby Theresia; Tjiptoleksono, Tjiptoleksono; Mus, Sukirno (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Theaim of the studywas to identify the isolated fungi from skipjack (Katsuwonus pelamis) katsuobushi during the fermentation process by using macroscopic and microscopic method and thento evaluate theorganoleptic characteristics of katsuobushi produced. The method used was descriptive which explained the process of making katsuobushi, the description of theisolated fungi whichwas grown in katsuobushi and the identification of the fungi macroscopically and microscopically, and also the proximate composition, including moisture content, ash content, pH value and total phenol content. The result showed that some species of fungi grown on the surface of katsuobushi during fermentation areAspergillus nigger, Aspergillus parasiticus, Aspergillus oryzae, Penicillium sp andFusarium sp. The katsuobushi fermentation process for 3 weeks indicated the higest organoleptic values,namely the value of appearance 7.7, odor 7.8, and taste 7.7. The chemical characteristics showed that the moisture content during the fermentation process was16.0 % for a week, 18.6 %for two weeks and 18.9 % for three weeks, but all were still under the value determined by the Indonesian Nasional Standards.The total number of microbia during fermentation was 4.3 x 103 CFU/gfor a week, 2.3 x 103CFU/gfor two weeks, 2.8 x 103 CFU/g forthree weeks,and 4.1 x 103 CFU/g for four weeks.All were also still under the value determined by the Indonesian Nasional Standards. Key words :Fermentation, Fungi, Isolation,Katsoubushi, Skipjack